Penerapan Teori Pembelajaran Van Hiele Berbantuan Geogebra untuk Meningkatkan Kemampuan Representasi Matematis Siswa Kelas VIII SMP Negeri 2 Sibolga - Retno Enjelita Hutasoit; Nurhasanah Siregar (Departement of Mathematics Education, 2024)
This study aims to see how the improvement of mathematical representation skills of class VIII students totaling 25 students at SMP Negeri 2 Sibolga in the 2022/2023 academic year after being subjected to learning that applies Van Hiele theory assisted by Geogebra. The type of research is Classroom Action Research with procedures that have repeated stages in Cycle I and Cycle II, namely problems, action planning, action implementation, observation, data analysis and reflection. The research began by finding that the average mathematical representation ability of students before the action was still in the low category, namely 48.8 with a percentage of 20% classical completeness, then the average ability increased to 70.67 (high) with 60% classical completeness in cycle I, and 87.25 (high) with 80% classical completeness in cycle II. The increase managed to go higher, seen from the increase in the gain index value which in cycle I was 0.39 (low) to 0.75 (high). In Indicator 1, the representation ability increased from 44 (low) to 63 (medium) then to 81.5 (high). Indicator 2 ability increased from 46 (low) to 67.66 (medium) then to 88.25 (high). In Indicator 3, the ability increased from 54 (medium) to 78.5 (high). In addition, the ability of the teacher/researcher in processing classroom activities increased significantly which in cycle I was 2.32 with a sufficient category to 3.03 with a good category. Then, the percentage of student activity also increased from 61.1% with a sufficient category to 82.4% with a high category. Through the results of this study, it can be concluded that the application of Van Hiele Theory with Geogebra assistance can improve the Mathematical Representation skills of 8th grade students of SMP Negeri 2 Sibolga in the 2022/2023 academic year.